Synergy of Competence and Mental Well-being in Achieving Offshore Fleet Operational Targets: The Mediating Role of Organizational Commitment - Ansar; Alwi Sibali; Gunawan; Umi Farida; Mattalatta; Kurniawaty (Journal of Indonesian Scholars for Social Research, 2026)
This study explores the critical synergy between technical competence and mental well-being in driving the operational success of offshore maritime fleets. Amidst a recorded decline in performance targets at SKOM Sdn. Bhd. (SK Offshore & Marine) from 2021 to 2023, this research identifies the underlying factors influencing ship crew productivity. Using a quantitative confirmatory design, data were collected from 213 crew members across 10 offshore vessels and analyzed through Structural Equation Modeling (SEM). The findings demonstrate that while technical training and the implementation of the International Safety Management (ISM) Code directly enhance operational execution, their long-term impact is heavily dependent on the psychological state of the crew. Job stress was found to significantly undermine both performance and organizational attachment. Crucially, the study reveals that organizational commitment acts as a vital bridge; it translates training and safety protocols into sustained high performance while mitigating the negative effects of occupational stress. These results suggest that achieving offshore operational targets requires more than just procedural compliance; it demands an integrated management approach that prioritizes mental health support alongside technical development. The study provides strategic recommendations for maritime managers to balance workload distribution and strengthen crew commitment to ensure operational reliability in high-risk environments.